Genetic Drift Versus Climate Region Spreading Dynamics of COVID-19 - Di Pietro, R.; Basile, M.; Antolini, L.; Alberti, S. (Frontiers in Genetics, 2021)
Background Current propagation models of COVID-19 are poorly consistent with existing epidemiological data and with evidence that the SARS-CoV-2 genome is mutating, for potential aggressive evolution of the disease. Objectives We searched fundamental variables that were missing from current analyses. Among them, regional climate heterogeneity, viral evolution processes versus founder effects and large-scale virus containment measures. Methods We challenged regional versus genetic evolution models of COVID-19 at a whole-population level, over 168,089 laboratory-confirmed SARS-CoV-2 infection cases in Italy, Spain and Scandinavia. Diffusion data in Germany, France and UK provided a validation dataset of 210,239 additional cases. Results Mean doubling time of COVID-19 cases was 6.63 days in Northern versus 5.38 days in Southern Italy. Spain extended this trend of faster diffusion in Southern Europe, with a doubling time of 4.2 days. Slower doubling times were observed in Sweden (9.4 days), Finland (10.8 days), Norway (12.95 days). COVID-19 doubling time in Germany (7.0 days), France (7.5 days) and UK (7.2 days) supported the North/South gradient model. Clusters of SARS-CoV-2 mutations upon sequential diffusion were not found to clearly correlate with regional distribution dynamics. Conclusions Acquisition of mutations upon SARS-CoV-2 spreading did not distinctly associate to enhanced virus aggressiveness, and failed to explain regional diffusion heterogeneity at early pandemic times. Our findings indicate that COVID-19 transmission rates associate to a sharp North/South climate gradient, with faster spreading in Southern regions. Thus, warmer climate conditions may not limit SARS-CoV-2 infectivity. Very cold regions may be better spared by recurrent courses of SARS-CoV-2 infection.